A convolutional neural network based feature learning and fault diagnosis method for the condition monitoring of gearbox. (December 2017) - Jing, Luyang; Zhao, Ming; Li, Pin; Xu, Xiaoqiang
Graphical abstract: Highlights: A CNN based feature learning and fault diagnosis method for gearboxes is proposed. The performance of feature learning of CNN with various data types is tested. The selection of key parameters of CNN is discussed. Feature learning with CNN provides better results than manual feature extraction. CNN is more suitable to learn features from vibration signal in frequency domain. Abstract: Feature extraction plays a vital role in intelligent fault diagnosis of mechanical system. Nevertheless, traditional feature extraction methods suffer from three problems, which are (1) the requirements of domain expertise and prior knowledge, (2) the sensitive to the changes of mechanical system and (3) the limitations of mining new features. It is attractive and meaningful to investigate an automatic feature extraction method, which can adaptively learn features from raw data and discover new fault-sensitive features. Deep learning has been widely used in image analysis and speech recognition with great success. The key advantage of this method lies into the ability of mining representative information and sensitive features from raw data. However, the application of deep learning in feature leaning for mechanical diagnosis is still few, and limited studies have been carried out to compare the effectiveness of feature leaning with various data types. This paper will focus on developing a convolutional neural network (CNN) to learn features directly from frequency data of vibration signals and testing the different performance of feature learning from raw data, frequency spectrum and combined time-frequency data. Manual features from time domain, frequency domain and wavelet domain as well as three common intelligent methods are used as comparisons. The effectiveness of the proposed method is validated through PHM 2009 gearbox challenge data and a planetary gearbox test rig. The results demonstrate that the proposed method is able to learn features adaptively from frequency data and achieve higher diagnosis accuracy than other comparative methods.